The Past, Present, and Future of Virtual and Augmented Reality Research: A Network and Cluster Analysis of the Literature - Cipresso, Pietro; Giglioli, Irene Alice Chicchi; Raya, Mariano Alcañiz; Riva, Giuseppe (Frontiers in Psychology, 2018)
The recent appearance of low cost Virtual Reality (VR) technologies – like the Oculus Rift, the HTC Vive and the Sony PlayStation VR – and Mixed Reality Interfaces (MRITF) – like the Hololens – is attracting the attention of users and researchers suggesting it may be the next largest stepping stone in technological innovation. However, the history of VR technology is longer than it may seem: the concept of VR was formulated in the 1960s and the first commercial VR tools appeared in the late 1980s. For this reason, during the last twentyyears, hundreds of researchers explored the processes, effects and applications of this technology producing thousands of scientific papers. What is the outcome of this significant research work? This paper wants to provide an answer to this question by exploring, using advanced scientometric techniques, the existing research corpus in the field. We collected all the existent articles about VR in the Web of Science Core Collection scientific database, and the resultant dataset contained 21,667 records for VR and 9,944 for AR. The bibliographic record contained various fields, such as author, title, abstract, country, and all the references (needed for the citation analysis). The network and cluster analysis of the literature showed a composite panorama characterized by evolutions over the time. Indeed, whether until five years ago, the main publication media on VR concerned both conference proceeding and journals, more recently journals constitute the main medium. Similarly, if at first computer science was the leading research field, nowadays clinical areas increased, as well as the number of countries involved in virtual reality research. The present work discusses the evolution of the use of virtual reality in the main areas of application with an emphasis on the future expected virtual reality’s capacities, increases and challenges. We conclude considering the disruptive contribution that VR/AR/MRITF will be able to get in scientific fields, as well in human communication and interaction, as already happened with the advent of mobile phones by increasing the use and the development of scientific applications (e.g. in clinical areas) and by modifying the social communication and interaction among people.